Error Analysis on Students’ Writing of Narrative Text Made by Fourth Semester Students at English Education Study Program of Batanghari University Year 2017/2018 - Reki Anggara, Wennyta, Khidayatul Munawwaroh (JELT: Journal of English Language Teaching, 2018)
Reki Anggara; Wennyta; Khidayatul MunawwarohAbstractThis research aims to find out the kind of students errors in writing narrative text in the fourth semester students at English Education Program of Batanghari University year 2017/2018. This research using purposive sampling to get the sample from two class and then got the 4th semester A class with the total 25 students. In collecting the data, the instrument of this research is writing test by using narrative text with theme exeperience during holidays. The findings of this research showed that, the error analysis writing narrative text in language features and generic structure. In language features, the most of errors were past tense with 4,35% percentage of error from 25 students. In generic structure, the most of errors was spelling with 6,74% percentage of errors from 25 students and orientation no errors from 25 students. The researcher concluded that the error analysis on students’ writing narrative text made by fourth semester students A class at english education program of Batanghari University year 2018 is good because from 25 student only two dominant errors in narrative text are past tense and spelling.Keywords: Error Analysis, Writing, and Narrative Text